Interactions between white genes carried by a large transposing element and the zeste[1] allele in Drosophila melanogaster. - Gubb, D.; Roote, J.; McGill, S.; Shelton, M.; Ashburner, M. (Genetics, 1986)
TE146, a large transposing element of Drosophila melanogaster, carries two copies of the white and roughest genes in tandem. In consequence, z(1)w( 11E4); TE146(Z)/+ flies have a zeste (lemon-yellow) eye color. However, one in 10(3)TE146 chromosomes mutates to a red-eyed form. The majority of these "spontaneous red" (SR) derivatives of TE146 have only one copy of the white gene and are, cytologically, two- to three-banded elements, rather than six-banded as their progenitor. The SR forms of TE146 are also unstable and give zeste-colored forms with a frequency of about one in 10(4). One such "spontaneous zeste" (SZ) derivative carries duplicated white genes as an inverted, rather than a tandem, repeat. The genetic instability of this inverted repeat form of TE146 is different from that of the original tandem repeat form. In particular, the inverted repeat form frequently produces derivatives with internal rearrangements of the TE and gives a much lower frequency of SR forms. In addition, two novel features of the interaction between w(+) alleles in a zeste background have been found. First, copies of w( +) can become insensitive to suppression by zeste even when paired. Second, an inversion breakpoint may disrupt the pairing between two adjacent w(+) alleles, necessary for their suppression by zeste, without physically separating them.